2013
DOI: 10.1074/jbc.m113.515668
|View full text |Cite
|
Sign up to set email alerts
|

Chemotype-selective Modes of Action of κ-Opioid Receptor Agonists

Abstract: Background:The -opioid receptor can be activated by structurally diverse agonists. Results: Four structurally diverse agonists differentially bound to and activated wild type and mutant -opioid receptors. Conclusion:The structural features of the agonists dictate how they interact with and stabilize G i -signaling receptor conformations. Significance: The results provide insights into the structural basis of opioid receptor ligand recognition and activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
140
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(160 citation statements)
references
References 44 publications
13
140
1
Order By: Relevance
“…In addition, it has been found that virtual screening for ligands using inactive-state GPCRs can produces agonist leads (see for example Negri et al) [27]. We have previously described a putative binding mode for salvinorin A representing an initial recognition mode based on an extensive amount of experimental data [9,28]. This binding mode was reproduced in the current docking studies and is shown in Figure 3a.…”
Section: Molecular Modelingsupporting
confidence: 56%
See 1 more Smart Citation
“…In addition, it has been found that virtual screening for ligands using inactive-state GPCRs can produces agonist leads (see for example Negri et al) [27]. We have previously described a putative binding mode for salvinorin A representing an initial recognition mode based on an extensive amount of experimental data [9,28]. This binding mode was reproduced in the current docking studies and is shown in Figure 3a.…”
Section: Molecular Modelingsupporting
confidence: 56%
“…Default parameters were used unless otherwise noted. The molecular modeling methods employed here are analogous to those previously published (see Wu, et al, [9] Vardy, et al [28] and references within).…”
Section: 32mentioning
confidence: 99%
“…It is interesting to note that most κOR ligands, particularly Sal A, exhibit nanomolar affinity for κOR. Interestingly, docking studies using the crystal structure of hκOR bound to the antagonist JDTic suggest that different chemotypes of κOR ligands bind to the same pocket in the receptor (25). We find that epimerization of Colly at C9 reduces agonist binding and signaling.…”
Section: Discussionmentioning
confidence: 73%
“…To investigate the role of the vicinal C-terminal cysteine moiety, we introduced a number of eight-membered ring mimetics (Figure 4). Replacement of cysteine by homocysteine either individually or together yielded analogues with extended ring sizes (49,50) resulting in a significant loss of KOR affinity. Replacement of the disulfide bond by a diseleno bond (35 → 52) or a sulfurseleno bond (26 → 53) was possible without loss of affinity, but no metabolic stability improvement was observed.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…48 The recent X-ray structure of KOR in complex with an antagonist (JDTic; (3R)-7-hydroxy-N-[(2S)-1-[(3R,4R)-4-(3-hydroxyphenyl)-3,4-dimethylpiperidin-1-yl]-3-methylbutan-2-yl]-1,2,3,4-tetrahydroisoquinoline-3-carboxamide) 49 has been used to confirm earlier docking results and is supported by receptor mutagenesis and functional studies. 50 The consensus view is that the YGGF message domain interacts with KOR in a similar way as the antagonist JDTic, encompassing a conserved opioid receptor hydrophobic pocket comprising W124 (ECL1) , V134 (3.28) , I135 (3.19) , and C210 (ECL2) . Additionally the D138 (3.32) carboxylate interaction with the Y1-amine residue is also critical for high affinity interactions.…”
Section: ■ Introductionmentioning
confidence: 99%